Interdependence and contributions of sun exposure and vitamin D to MRI measures in multiple sclerosis. Issue 10 (5th February 2013) - Zivadinov, Robert; Treu, Cierra N; Weinstock-Guttman, Bianca; Turner, Caitlin; Bergsland, Niels; O'Connor, Kerri; Dwyer, Michael G; Carl, Ellen; Ramasamy, Deepa P; Qu, Jun; Ramanathan, Murali
Abstract : Purpose: To assess the relationships of sun exposure history, supplementation and environmental factors to vitamin D levels in multiple sclerosis (MS) patients and to evaluate the associations between sun exposure and MRI measures. Methods: This study included 264 MS patients (mean age 46.9±10 years, disease duration 14.6±10 years; 67.8% relapsing–remitting, 28% secondary progressive and 4.2% primary progressive MS) and 69 healthy controls. Subjects underwent neurological and 3 T MRI examinations, provided blood samples and answered questions to a structured questionnaire. Information on race, skin and eye colour, supplement use, body mass index (BMI) and sun exposure was obtained by questionnaire. The vitamin D metabolites (25-hydroxy vitamin D3, 1, 25-dihydroxy vitamin D3 and 24, 25-dihydroxy vitamin D3) were measured using mass spectrometry. Results: Multivitamin supplementation (partial correlation rp =0.29, p<0.001), BMI (rp =−0.24, p=0.001), summer sun exposure (rp =0.22, p=0.002) and darker eye colour (rp =−0.18, p=0.015) had the strongest associations with vitamin D metabolite levels in the MS group. Increased summer sun exposure was associated with increased grey matter volume (GMV, rp =0.16, p=0.019) and whole brain volume (WBV, rp =0.20, p=0.004) after correcting for Extended Disability Status Scale in the MS group. Inclusion of 25-hydroxy vitamin D3 levels did not substantially affect the positive associations of sun exposure with WBV (rp =0.18, p=0.003) and GMV (rp =0.14, p=0.026) in the MS group. Conclusions: Sun exposure may have direct effects on MRI measures of neurodegeneration in MS, independently of vitamin D.